Neuropsychiatric symptoms as the main determinant of caregiver burden in Alzheimer's disease - Renata Kochhann; Ericksen Borba; Maria Otília Cerveira; Diego Onyszko; Alyne de Jesus; Letícia Forster; Luisa Franciscatto; Cláudia Godinho; Ana Luiza Camozzato; Márcia Lorena F. Chaves (Dementia & Neuropsychologia)
Abstract Caregiver burden is common in Alzheimer's disease (AD), decreasing the quality of life among caregivers and patients. Projections of aging and aging-related diseases such as AD in developing countries justify additional data about this issue because people living in these countries have shown similarly high levels of caregiver strain as in the developed world. Objective: The aim of this study was to analyze the association of AD caregivers' burden with patients' neuropsychiatric symptoms (NPS), cognitive status, severity of dementia, functional capacity, caregiver sociodemographic characteristics, and the characteristics of care provided by caregivers. Methods: A cross-sectional study was conducted in a sample of 39 consecutive AD patients and their primary caregivers. NPS were evaluated using the Neuropsychiatric Inventory (NPI). Severity of dementia was assessed with the Clinical Dementia Rating (CDR) scale. Functional capacity was assessed using the Katz and Lawton scales. The burden level was rated using the Burden Interview (BI). Sociodemographic characteristics of caregivers and the characteristics of care provided by them were evaluated. The Mann-Whitney U-test, Kruskal-Wallis test and Spearman's rho coefficient were performed. Results: The BI had a moderate correlation with NPI intensity (rho=0.563), p<001. Female caregivers reported a greater level of burden (p=0.031) than male caregivers. The other variables were not significantly associated to caregiver burden. Conclusion: NPS were the main determinant of burden in primary caregivers of AD patients. This result underscores the need for prevention and treatment of these symptoms. Sex also had an effect on caregiver burden, but the small male sample in this study precludes the generalization of this finding.